The organizational setup and integrated values of the Maersk Line Company - Smielecki Gilbert (My University, 2008)
The purpose of this thesis is to explore the nature of organizations and organizational theory. The organizational setup is perhaps the most important aspect to regularly revisit, but seldom done. It always brings surprises and shows how much can be adjusted internally, rather than seeking for new opportunities outside the company. By focusing on organizational layers and the decision making process, we can reduce the complexity as well as the time it takes to make a decision. Sometimes, giving employees the authority gives more than hiring experience employees. Also, paying attention to unjustified costs on a daily basis may be a better option than any cost reduction incentive. Many companies fail in taking the necessary actions to build the probability of successful organizational upgrade. There are many examples of adjusting the financial figures by amateur financial engineering, of fantasy approach to the dot-com business. In fact, the organizational setup should be the main focus and the essential pare of all activities. This thesis is describing the Maersk Line and its recent organizational change. For a big company, operating globally it is hard to find one solution, as there are many possible scenarios. In fact it is hard to predict changes in the market and within competition. This stud shows and describes the way and different approach ad certain organizational stages. A story of a successful company, for which its size became the internal issue – so important, that immediate changes were required. Chapter one describes the theoretical approach to organizational structures. It gives the concept and importance, as well as the relationship between different elements within the structure. The overview of key elements helps in understanding the purpose of the organizational analysis and the advantages it may bring, when properly implemented. Chapter two is an overview of the A.P. Moller Maersk Group and its daughter companies, with focus on Maersk Line – the global leader providing containerized ocean and inland services. The containerization process as such and the history of containerization are also described in this chapter. In Chapter three we will find the description of the organizational setup and the integrated values applied to the structure. A detailed overview of the old and the new structure will help in understanding the whole process of a global organizational change and reasons for doing so. Chapter four describes the change itself, the timeframe and strategic objectives. A top-down analysis gives a clear picture of the process and the final result, giving a chance for understanding the need of change and the advantages it may bring for future company’s effectiveness.
Zmiany w strukturze i systemie wartosci organizacji na przykladzie firmy Maersk Line
Keywords: organization; organizational design; organizational culture; organizational change